Experiences with Fertility Reduction in Five High-Fertility Countries : Synthesis of Case Studies - World Bank (World Bank, Washington, DC, 2017)
Countries with high levels of fertility lag behind others in development indicators and in progress toward the Millennium Development Goals. While several developing countries have lowered fertility rates over the last three decades, huge challenges remain. The family planning needs of some 137 million married women in developing countries are still unmet. About a third of the approximately 205 million pregnancies each year are unintended, and half of induced abortions performed globally are unsafe. Some 28 countries, mainly in Sub-Saharan Africa, have a total fertility rate greater than 5, and the decline in fertility rates has been very slow or has stalled. In most countries, national averages mask substantial differences in fertility levels between the well-off and the poor, highlighting equity concerns. The objective of this study is not to repeat those discussions and findings but rather to provide evidence-based, relevant, and practical information on population and family planning issues to stimulate policy dialogue with client countries and influence World Bank lending in countries that still have high fertility rates.